2007
DOI: 10.1016/j.alcohol.2007.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Maternal alcohol ingestion reduces surfactant protein A expression by preterm fetal lung epithelia

Abstract: In addition to neurodevelopmental effects, alcohol consumption at high levels during pregnancy is associated with immunomodulation and premature birth. Premature birth, in turn, is associated with increased susceptibility to various infectious agents such as Respiratory Syncytial Virus (RSV). The initial line of pulmonary innate defense includes the mucociliary apparatus, which expels microorganisms trapped within the airway secretions. Surfactant proteins A and D (SP-A and SP-D, respectively) are additional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 64 publications
8
45
1
1
Order By: Relevance
“…Our findings are in agreement with a recent study in sheep that showed that prenatal ethanol exposure decreases SP-A mRNA and protein levels (36). That study also demonstrated that prenatal ethanol exposure inhibits stimulated tracheal ciliary beat frequency, which is a protective mechanism required to remove foreign particles from the lungs (36). These findings are consistent with other studies that show that ethanol has an overall immunosuppressive effect (17,(22)(23)(24)27).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings are in agreement with a recent study in sheep that showed that prenatal ethanol exposure decreases SP-A mRNA and protein levels (36). That study also demonstrated that prenatal ethanol exposure inhibits stimulated tracheal ciliary beat frequency, which is a protective mechanism required to remove foreign particles from the lungs (36). These findings are consistent with other studies that show that ethanol has an overall immunosuppressive effect (17,(22)(23)(24)27).…”
Section: Discussionsupporting
confidence: 83%
“…SP-A and SP-D can bind and opsonize microorganisms and, therefore, can have an important role in the lung's primary defense against inhaled pathogens, as well as being an important component of the innate immune response of the lungs. Our findings are in agreement with a recent study in sheep that showed that prenatal ethanol exposure decreases SP-A mRNA and protein levels (36). That study also demonstrated that prenatal ethanol exposure inhibits stimulated tracheal ciliary beat frequency, which is a protective mechanism required to remove foreign particles from the lungs (36).…”
Section: Discussionsupporting
confidence: 83%
“…In summary, these fi ndings support our claim that PREXCEL-Q-calculated nucleic acid sample and standard dilutions for qPCR, based on the "Stock I approach" (Grubor et al, 2004;Gallup et al, 2005;Gallup et al, 2006;Kawashima et al, 2006;Lazic et al, 2007;Gallup et al, 2008;Olivier et al, 2009;Sponseller et al, 2009), avoids qPCR inhibitory behavior in all fi nal reactions (Gallup et al, 2008;. Because of this and other aspects, we recommend the use of PREXCEL-Q in all laboratories performing qPCR of any kind.…”
Section: Spud Plasmid Spud Ampliconsupporting
confidence: 71%
“…PREXCEL-Q is a qPCR software program that, among its other functions, identifies dilution parameters for all samples and standards that avoid qPCR-inhibitory phenomena. The SPUD assay was thus used in this study to critically test and corroborate the reported ability of the PREXCEL-Q program to avoid inhibition in qPCR samples and standards (Grubor et al, 2004;Gallup et al, 2005;Gallup et al, 2006;Kawashima et al, 2006;Lazic et al, 2007;Gallup et al, 2008;Olivier et al, 2009;Sponseller et al, 2009). …”
Section: Introductionmentioning
confidence: 98%
“…Studies in rodents have also shown that exposure to high levels of ethanol in midgestation (41) or throughout pregnancy (23) decreases fetal lung growth. In contrast, exposure to a moderate level of ethanol during the later stages of gestation in sheep, when structural and functional maturation of the lungs occurs, does not alter fetal lung growth (37), although collagen deposition in the fetal lungs is increased and surfactant protein (SP) levels are reduced (28,37).…”
mentioning
confidence: 89%